2022
DOI: 10.1039/d2an00792d
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation and isomeric differentiation/quantitation of monophosphorylated phosphoinositides using gas-phase ion/ion reactions and dissociation kinetics

Abstract: Phosphoinositides, phosphorylated derivatives of phosphatidylinositols, are essential signaling phospholipids in all mammalian’s cellular membranes. With three known phosphorylated derivatives of phosphatidylinositols at the 3-, 4-, and 5- positions along the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…To explore this possibility, we applied dipolar DC (DDC) collisional activation, a broadband activation technique. We have previously reported various implementations of DDC. ,,, It has been demonstrated that by changing the applied time of DDC while keeping the voltage constant, pseudo-first-order kinetics are observed, and thus, dissociation rates can be determined. Dissociation rate determination has been able to offer fundamental insights into topics such as gas-phase covalent bond formation energetics, , determining effective ion temperatures, and lipid isomeric differentiation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore this possibility, we applied dipolar DC (DDC) collisional activation, a broadband activation technique. We have previously reported various implementations of DDC. ,,, It has been demonstrated that by changing the applied time of DDC while keeping the voltage constant, pseudo-first-order kinetics are observed, and thus, dissociation rates can be determined. Dissociation rate determination has been able to offer fundamental insights into topics such as gas-phase covalent bond formation energetics, , determining effective ion temperatures, and lipid isomeric differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported using divalent alkaline earth metals complexed with tris 1,10-phenanthroline (phen) and 2,2′:6′,2″-terpyridine (terpy) to charge-invert singly charged lipid species that allowed for in-depth structural characterization and isomeric differentiation. However, larger lipids such as Lipid A, cardiolipin, and phosphatidylinositol phosphate , preferentially ionize as dianions, precluding divalent metal complexes as suitable reagents for ion/ion reactions due to inevitable neutralization.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike single-frequency IT-CID, both precursor and product ions experience RF heating, which leads to sequential fragmentation, particularly at long DDC-CID times. For the measurement of the fragmentation rate of a precursor ion, DDC-CID is preferred because it is much less tuning-sensitive relative to single-frequency IT-CID. , In the DDC experiment presented here, ions are isolated in Q1 and stored in q2, where they are collisionally cooled for 0.04 s. DDC-CID is then applied to q2 for a specified range between 0.05 and 0.7 s for this experiment. Ions are then cooled again for 0.03 s before being sent to the detector for 0.13 s.…”
Section: Methodsmentioning
confidence: 99%
“…Dissociation rates under DDC-CID activation conditions follow pseudo-first-order kinetics, as indicated in eq . false[ M false] t = e k diss t false[ M false] t = P t × A P t + F t , goodbreak0em2em⁣ where .25em A = TI C t TI C 0.05 where [ M ] t is the mole fraction or survival yield of the precursor ion at time t , k diss is the dissociation rate, and TIC is the total ion count. The survival yield (eq ) is determined by dividing the residual precursor signal by the sum of the residual precursor signal ( P t ) and all identified product ions ( F t ).…”
Section: Methodsmentioning
confidence: 99%
“…Tandem mass spectrometry is widely employed for the primary structural characterization of polyatomic ions via dissociation reactions induced by one or more dissociation methods. Structural information is usually inferred from the identities of the product ions. However, under appropriate conditions, dissociation kinetics can be useful in distinguishing isomeric ions that yield the same product ions and can reveal both energetic and dynamic information about dissociation pathways . Slow heating methods, including both collision- and light-mediated energy transfers, lend themselves particularly well to the measurement of dissociation kinetics in ion trapping instruments.…”
Section: Introductionmentioning
confidence: 99%